A 32‐society investigation of the influence of perceived economic inequality on social class stereotyping. (8th November 2022) - Tanjitpiyanond, Porntida; Jetten, Jolanda; Peters, Kim; Ashokkumar, Ashwini; Barry, Oumar; Billet, Matthew; Becker, Maja; Booth, Robert W.; Castro, Diego; Chinchilla, Juana; Costantini, Giulio; Dejonckheere, Egon; et al.
Abstract: There is a growing body of work suggesting that social class stereotypes are amplified when people perceive higher levels of economic inequality—that is, the wealthy are perceived as more competent and assertive and the poor as more incompetent and unassertive. The present study tested this prediction in 32 societies and also examines the role of wealth‐based categorization in explaining this relationship. We found that people who perceived higher economic inequality were indeed more likely to consider wealth as a meaningful basis for categorization. Unexpectedly, however, higher levels of perceived inequality were associated with perceiving the wealthy as less competent and assertive and the poor as more competent and assertive. Unpacking this further, exploratory analyses showed that the observed tendency to stereotype the wealthy negatively only emerged in societies with lower social mobility and democracy and higher corruption. This points to the importance of understanding how socio‐structural features that co‐occur with economic inequality may shape perceptions of the wealthy and the poor.